Evaluation of Oxidative DNA Damage and Immunity Markers as Predicate of Prostate Patients - Hameed Ali, Saja; Hammood, Samah Amer (Journal of Neonatal Surgery, 2025)
Problems in health male accounts for 50% of all occurrences of infertility and is the only cause of 10–30% of cases. Male-specific malignancies and reproductive problems have become a major public health concern due to their sharp rise in recent years. Study Aim: In this research, the levels of some different biomarkers will be investigated –Prostatic Acid Phosphatase (PAP), Prostate Cancer Gene 3 (PCA3), reactive oxygen species 8-hydroxy-2'-deoxyguanosine (8-OHDG), and immunological cytokines including IL-18 and prostate specific antigen (PSA) at the fertility center as a diagnostic marker of hyperplasis between patients who were infertile due to prostate cancer, patients who had prostatic hyperplasia, and healthy individuals who were fertile controls. Material and methods: The study involved 100 males, choose 80 divided into 58 prostate hyperplasia male infertile, 10 fertile control male and 22 patients' prostatic cancer infertile visit the fertility center and Doctor's Consulting Clinic in peroid between 1/11/2024 to 1/3/2025. Results: Significant differences in biomarker levels were observed across the groups. The levels of IL-18, PSA, PAP, and PCA3 were also considerably higher in patients with hyperplasia and cancer when compared to the levels seen in controls (The p-value for PAP was less than 0.01, the p-value for PCA3 was less than 0.002, and the p-value for IL-18 was less than 0.001). Notably, 8-OHDG levels were significantly lower in hyperplasia and cancer groups compared to controls (p < 0.05). While mean values for PCA3 and IL-18 were higher in cancer than hyperplasia, these differences did not reach statistical significance also, PAP demonstrated clear differences between all three groups and 8-OHDG was significantly lower in disease groups compared to controls. Conclusion: These results suggest that, 8-OHDG, PAP, PCA3, PSA, and IL-18 may serve as valuable biomarkers for differentiating between healthy individuals, those with prostatic hyperplasia, and those with prostate cancer. Recommendation: These biomarkers have potential clinical utility in distinguishing prostate health and disease states, conduct more in-depth studies to explore the relationship between BMI and P. Hyperplasia/Cancer 8-OHDG, PAP, PCA3, PSA, and IL-18 and investigate potential mechanisms, such as hormonal influences, inflammatory markers, and metabolic factors.